Volunteer management beyond prescribed best practice: a case study of Portuguese non-profits. Issue 2 (6th March 2017) - Carvalho, Ana; Sampaio, Martinha
Abstract : Purpose: The purpose of this paper is to complement and test prescriptive volunteer management proposals by examining how volunteers are actually managed and exploring factors other than prescribed best practice to assess volunteer management effectiveness. Design/methodology/approach: The authors use qualitative methods to study five Portuguese non-profit organisations, selected for having active volunteer programmes while presenting diverse sizes, organisation styles and levels of reliance upon volunteers. Interviews were conducted between February and August 2011 with board representatives, volunteer managers and volunteers. Findings: This paper assesses volunteer management practices in these organisations, and further identifies a number of interrelated dimensions affecting volunteer programme success, namely: centrality, formalisation, professional support, sustainability and a minimum set of practices. It also uncovers weakness points that inhibit further development, including lack of a strategic approach and limited capacity to diversify sources of financing. Research limitations/implications: This is an exploratory study, with a limited number of cases and interviews. Practical implications: This study may help volunteer managers focus their attention in aspects other than prescribed management practice. Although a minimum set of identified practices are vital, the dimensions it uncovers have a pivotal role in the success of volunteer programmes. Originality/value: This set of intertwined dimensions has not been specifically addressed in the literature. They go beyond the more conventionally prescribed volunteer management practices, and provide a promising framework for analysing the effectiveness and sustainability of volunteer management.